INTEGRATED MANAGEMENT OF FOOT ROT OF BETELVINE CAUSED BY SCLEROTIUM ROLFSII (Journal of Plant Disease Sciences, 2017)
Betel vine ( L.) is a Piper betel perennial dioecious creeper belonging to the family . It is a climbing plant with Piperaceae shiny, green, heart-shaped leaves and white catkin. The stem is climbing by many short adventitious roots (Hassan and Shahadat, 2005). Among the diseases of betel vine, foot and root rot caused by Sacc. Sclerotium rolfsii are the most devastating diseases which decrease the production of betel vine to a great extent, causing losses up to 29-90%. Sclerotium rolfsii Sacc. is a soil borne pathogenic fungus and harmful to many crops which are economically valuable in most of the tropical and subtropical region of the world (Aycock, 1966). It has a wide host range and has been referred as an almost omni pathogenic organism. The fungus is a facultative parasite and can maintain continuity of generation under adverse situation by the formation of sclerotia. It is very difficult to control even by the use of chemical fungicide. As a creeper crop the basal part of the betel vine stem to be kept in soil by folding and it's a continuous process as the part of the cultivation practice. The stem kept in the soil are often become affected by the soil borne fungus The Sclerotium rolfsii. basal part of the stem become rotten and caused a huge loss i.e. reduces the quality of betel leaf and hence the farmers are deprived from the usual market price. Therefore, an integrated disease management approach that encompass the use of chemicals, bio-control agents, phytoextracts and soil amendments, could be the most economical and effective strategy to manage diseases.
Keywords: Foot rot, Beetle vine, Bioagents, IDM. Sclerotium rolfsii